Inflammation, Immune Activation, Immunosenescence, and Hormonal Biomarkers in the Frailty-Related Phenotype of Men With or at Risk for HIV Infection. (31st October 2016) - Erlandson, Kristine M.; Ng, Derek K.; Jacobson, Lisa P.; Margolick, Joseph B.; Dobs, Adrian S.; Palella, Frank J.; Lake, Jordan E.; Bui, Hanhvy; Kingsley, Lawrence; Brown, Todd T.
Abstract : Background: The extent to which inflammation, immune activation/immunosenescence, and hormonal abnormalities are driven by human immunodeficiency virus (HIV) or frailty is not clear. Methods: HIV-infected frail men (n = 155) were matched to nonfrail, HIV-infected (n = 141) and HIV-uninfected (n = 150) men by age, calendar year, and antiretroviral therapy use (HIV-infected men only). Frailty was defined by ≥3 frailty-related phenotype criteria (weight loss, exhaustion, low activity, slowness) at ≥2 visits, or at 1 visit with ≥1 criteria at ≥2 visits. The following measurements were obtained: interleukin 6, high-sensitivity C-reactive protein, soluble receptors for tumor necrosis factor α 1 and 2, the percentages of CD4 + CD28 −, CD8 + CD28 −, CD4 + CD38 + HLA-DR +, and CD8 + CD38 + HLA-DR + T cells, dehydroepiandrosterone sulfate, free testosterone, homeostatic model assessment of insulin resistance, and insulin-like growth factor 1. Log-linear regressions were adjusted for a priori selected covariates to determine differences by frailty and HIV status. Results: In multivariate analyses adjusted for covariates, frailty was associated among HIV-infected men with higher interleukin 6 and high-sensitivity C-reactive protein and lower free testosterone and dehydroepiandrosterone levels. In contrast, HIV infection but not frailty was associated with significantly greater immune senescence (percentage of CD4 + CD28 − or CD8 + CD28 − T cells) and immune activation (percentages of CD4 + CD38 + HLA-DR + and CD8 + CD38 + HLA-DR + T cells). Conclusions: Frailty among HIV-infected men was associated with increased inflammation and lower hormone levels, independent of comorbid conditions. Interventions targeting these pathways should be evaluated to determine the impact on prevention or reversal of frailty among HIV-infected men.